Emotional contagion in adult English education: a self-narrative study of teacher–student interactions in Yangshuo County - Hongji Jiang (Frontiers in Psychology)
This study aims to explore the emotional contagion dynamics between adult English learners and their teacher, focusing on the interplay of positive and negative emotional expressions across different proficiency levels and the pivotal role of learners as emotional initiators in shaping teacher–student interactions. Using a self-narrative study method, qualitative data were collected through interviews, informal exchanges, and reflective teaching logs involving 10 adult English learners at a private language training institution in Yangshuo County, China. As both the teacher and researcher, I captured and analyzed emotional exchanges, identifying three negative emotions: students’ anxiety, which triggered self-doubt in the teacher; students’ confusion, which led to the teacher’s disappointment; and students’ discontent, which evoked anger in the teacher. In contrast, two positive emotions were observed among intermediate and advanced learners: students’ calm fostering the teacher’s tranquility, and students’ happiness bringing the teacher relief. The findings challenge traditional assumptions by identifying adult learners as primary initiators of emotional contagion, with teachers often responding to these emotional cues. This study highlights how cultural norms, such as face-saving in China, and institutional pressures reshape teacher–student emotional dynamics. It provides practical implications for emotional regulation, culturally sensitive pedagogy, and the integration of communicative and traditional teaching methods, offering a foundation for future research on emotions in adult language learning contexts.